Preservation and Promotion of Traditional Culture of Ethnic Minorities in Tourism Development in Tuyen Quang Province, Vietnam - Thuy, Le Thi Bich; Thuong, Le Thi Thanh (International Journal of Humanities and Education Development (IJHED), 2025)
Preserving and promoting the traditional cultural values of ethnic minority communities will contribute to enriching their cultural heritage, strengthening unity and solidarity among ethnic groups, and creating a significant internal driving force for sustainable national development. Currently, ethnic minorities in Tuyen Quang Province still maintain their unique customs, traditions, and cultural practices. These are potential strengths and favorable conditions that contribute to the sustainable tourism development of Tuyen Quang Province, creating an appealing attraction for visitors to explore, discover, and experience the cultural tourism of Tuyen Quang.